Economic Education and Entrepreneurial Education in Romania - Ungureanu, Laura; Militaru, Petrişor (Journal of Research in Educational Sciences; Vol 2 No 2 (2011): JRES, Volume II, Issue 2(4), Winter 2011, 2011)
This paper presents the status of economic education in Romania and its challenges, considering the circumstances in today's evolving world and horizon of expectations to which it is heading. Because of its many dimensions, education is essential, but challenging. In the generic sense, the school - as educational institution - becomes a fundamental institution having a strategic vocation to society. Economic education - coupled with education for change and development - acquires importance, increasing its importance in a country located in a continuous transition, leading to reshuffle the optical and economic behaviour. Through its specific problems, economic education makes plea for training future consumers, employees and entrepreneurs in the spirit of free market economy. I tried to offer as far as possible, some openings in economic education research, targeting both the theoretical and methodological plan, as well as the strategic plan - operational, offering specialists and decision makers interested in possible courses of action they consider appropriate and current priority stage that crosses Romania. In relation to this objective, the analysis stressed the need for economic education and entrepreneurial needs manifested in all socio-professional categories. Finally we describe some directions and implications of economic and educational economist for initial and modern, in terms of personality adapting the Romanian society, focusing on traditional functions of university education and vocational training benefits continue. The paper concludes by proposing courses of action for improving economic education in Romania.